2006
DOI: 10.1063/1.2165088
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial with randomized patterns for negative refraction of electromagnetic waves

Abstract: Artificial metamaterials made to date are all periodic in structure. Here we show that by randomizing contour patterns deposited lithographically on circuit board materials, a metamaterial characterized by a constitutive relation with negative constitutive parameters is produced in solid-state form. We clearly demonstrate the phenomenon of negative refraction to show that it is not produced by periodicity. This underlines the importance of using constitutive relations for media characterization in electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Metafilms can be thought of as the bridge between three-dimensional (3D) metamaterials and the so-called frequency-selective surfaces [8]. The functionality of frequency-selective surfaces is based on the periodicity of the constituent elements, and is described by coherent wave interference concepts such as Bloch waves or Floquet modes [8][9][10]. Conversely, metafilms function on the same basis as metamaterials; their macroscopic properties depend mostly on the structure of the subwavelength resonators, and not necessarily on their periodic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Metafilms can be thought of as the bridge between three-dimensional (3D) metamaterials and the so-called frequency-selective surfaces [8]. The functionality of frequency-selective surfaces is based on the periodicity of the constituent elements, and is described by coherent wave interference concepts such as Bloch waves or Floquet modes [8][9][10]. Conversely, metafilms function on the same basis as metamaterials; their macroscopic properties depend mostly on the structure of the subwavelength resonators, and not necessarily on their periodic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental demonstration of the existence of negative refraction inside metamaterial composed of rings and wires was reported in 2001 [1], several studies aimed at verifying the existence of negative index metamaterials (NIMs) have been reported and exhibited [2][3][4][5][6][7][8]. The phenomenon of negative refraction, predicted to occur in NIMs obtained by a structured square split resonant ring and metal wire (SSRR-MW) metamaterial with simultaneously negative permittivity and negative permeability, has an important application in the electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…30,33,58,59 Subsequently, Gorkunov et al 60 theoretically demonstrated that the randomly distributed defects could profoundly influence the resonant properties of metamaterials, and the existence of defects might result in multiband magnetic responses. Then, Chen et al 61 experimentally confirmed negative refraction via a metamaterial with randomized contour patterns. Later, Yannopapas 62 further proposed a disordered binary photonic alloy composed of polaritonic and plasmonic microspheres that could achieve negative refractive index.…”
Section: The Defect Effect Of Lhmsmentioning
confidence: 99%